Development of Kinetic Model Structures for Glutinous Rice Saccharification by Different Enzymes. Issue 3 (16th April 2014) - Liu, Dengfeng; Zhang, Hongtao; Xu, Baoguo; Tan, Jinglu
Abstract Glutinous rice saccharification was performed with α‐amylase, glucoamylase, a two‐enzyme combination or wheat qu. Experiments were carried out at two locations, with rice from two sources and in different fermentation temperatures. The main products were first identified and then measured by high‐performance liquid chromatography. Low‐order kinetic model structures (constructs of model with adjustable reaction rates) were derived based on the major chemical reactions brought about by different enzymes. The model structures were then tested for their abilities to capture the main kinetic variations after optimization of reaction rates by a least square algorithm. The model structures were found useful in representing the measured kinetic variations with one exception. The estimated reactions rates correctly reflected the variations observed from the experiments and provided insights into the reaction processes in terms of reaction speeds, dominant variations and primary products. The actions of α‐amylase and wheat qu differed from findings in prior research. The proposed model structures show promise for describing the saccharification process of glutinous rice. Practical Applications Rice is routinely hydrolyzed as part of the processes to produce wines, alcohols, amino acids and other products. This research provides a set of model structures that are simple enough for practical use and still capture the main kinetic behaviors of the saccharification process with enzymes often used in industry. The model structures are needed by food process engineers in their efforts to analyze, optimize and develop controls for many industrial processes that involve rice saccharification.